2018
DOI: 10.1111/jgh.13865
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in celiac disease: Is it a common feature in children?

Abstract: Intussusception is frequently (25%) seen in children with newly diagnosed CD, generally asymptomatic and resolves spontaneously on GFD. It is often associated with more severe disease. Children with CD and intussusception should not be subjected to surgical/radiological intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
0
15
0
6
Order By: Relevance
“…Biopsy-proven CD had 1% prevalence in children. 2,5 Earlier celiac disease was considered uncommon in India, but studies showed overall sero-prevalence of CD as 1.44% and the overall prevalence of CD as 1.04%. The overall prevalence of CD in the north Indian community was 1 in 96, and 1 in 310 in school children of north India.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Biopsy-proven CD had 1% prevalence in children. 2,5 Earlier celiac disease was considered uncommon in India, but studies showed overall sero-prevalence of CD as 1.44% and the overall prevalence of CD as 1.04%. The overall prevalence of CD in the north Indian community was 1 in 96, and 1 in 310 in school children of north India.…”
Section: Discussionmentioning
confidence: 99%
“…Reported prevalence of intussusception with CD is around 1.6-20% and 1.2-25% in adults and children, respectively, but actual prevalence can be higher because of transient and asymptomatic presentation. 5,[8][9][10][11] Rarely, intussusception can be the initial presenting symptom of pediatric CD. 8,9 Spontaneous reduction of intussusception occurs in 4-10% of children and not uncommon even during preparation for operation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations